Teaching Methods: Irrelevancy of Teacher Centric Techniques in Classroom - Karki, Data Ram (KMC Research Journal, 2021)
The research paper surveys generic trend of teaching learning methods in formal educational institution in Nepal and it also observes departure in methodological shift from traditional world to the present one. Discussing about traditional methods in present techno friendly world, it raises questions of relevancy of them. The research critically examines existing teacher-centric methods in teaching learning and raises questions over relevancy of them in classroom teaching in Nepal. Teacher-centric methods are primarily used to deliver knowledge and information to the students and those students are assumed to have been unknown to the subject matter. Teacher is considered as omniscient and makes presentations in classroom. The methods are unable to make them interactive and communicative and cannot exchange their ideas in classroom. But, modern technologies have eased access to knowledge and information for everyone. Even students can have sufficient knowledge about subject matter to be taught in formal teaching learning activities. With sufficient knowledge about subject matters, students are expected to participate in interactive learning. The traditional way of delivering subject matter to students seems to be no longer effective in teaching when students are already familiar with the topic to be presented in classroom and teachers are unable to hold students’ attention. On the contrary, teachers would be source of knowledge in traditional teaching therefore teacher-centered techniques were dominant. The conventional role of teacher and teaching methods seem to have been irrelevant along with students’ access to knowledge and it has been possible along with the growing techno-friendly learning environment.